2020
DOI: 10.1111/jors.12484
|View full text |Cite
|
Sign up to set email alerts
|

Railways and manufacturing productivity in Italy after unification

Abstract: This paper contributes to the debate on the effects of transport infrastructure endowment on productivity by adding a historical perspective. This allows us to address the issue in a proving ground where the effects of the existing stock of infrastructure are negligible. At the time of unification, the Kingdom of Italy initiated a large infrastructure project to build railways. We find that railways had a positive effect on manufacturing productivity over the period 1871–1911. Railways also had strong spillove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…They find modest average effects, which are however considerably higher for northern regions. A similar analysis, but at the province level, is conducted by Pontarollo and Ricciuti (2020), who find a more homogenous positive effect of the railways.…”
Section: Railways and The Patterns Of Economic Activitymentioning
confidence: 73%
“…They find modest average effects, which are however considerably higher for northern regions. A similar analysis, but at the province level, is conducted by Pontarollo and Ricciuti (2020), who find a more homogenous positive effect of the railways.…”
Section: Railways and The Patterns Of Economic Activitymentioning
confidence: 73%
“…Transportation linkages have an adverse effect on health in the rural US (Zimran, 2019). Railroads manage to boost manufacturing productivity in US (Hornbeck and Rotemberg, 2019;Pontarollo and Ricciuti, 2020). Improvements in transport and communications technologies boost the employment in interactive occupations (Michaels et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study results showed that HSR has a positive influence on firm productivity. Thus, HSR can promote regional economic growth by improving the economic efficiency of enterprises (Pontarollo and Ricciuti, 2020). Second, the continuous improvement of HSR will break the market segmentation between cities (Vickerman, 2018).…”
Section: Introductionmentioning
confidence: 99%